Portable Grinder-Mixers - Harner III, Joseph P.; Herrman, Tim J. (My University, 1995)
This publication provides information pertaining to feed processing that will improve operating efficiency, feed quality, and regulatory compliance.
MF2054_1995_08
Keywords: MF2054; Equipment and structures; livestock; MF